The Use of English Songs to Improve Students Listening Skill at SMP Negeri 242 Jakarta - Fatimatuzzahro, Siti; Rodiyah, Siti; Rakhmawati, Ditta Mustika; Wahdini, Lili; Susandi, Deny Gunawan (CV. Ulil Albab Corp, 2024)
This Classroom Action Research (CAR) study investigates the efficacy of utilizing song media as an instructional tool to enhance students' listening abilities in English language teaching. The research was conducted in a VIII-C class at SMPN 242 Jakarta, involving 36 students. Employing a quantitative approach, pre-test and post-test cycles were conducted using questionnaire tests, song listening tests with multiple-choice questions, and essays to evaluate changes in students' perspectives and listening skills. The study revealed that, initially, only 40% of students enjoyed English classes, but after the integration of song media, this percentage increased to 70%. The pre-test scores indicated that 60% of students achieved a